Sanction For Liquor Providers From The Perspective Of Islamic Criminal Lw - Isliani, Yenni (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Sanctions are penalties given to a person who violates laws or rules aimed at providing a deterrent effect and reducing criminal acts. The formulation of the problem from this study is how are the sanctions for liquor providers according to Perda No.07 of 2015 in Padang Lawas Regency? and what is the review of Islamic criminal law against the sanctions of liquor providers according to Perda No.07 of 2015?. The purpose of this researcher is to find out the sanctions for liquor providers in the Padang Lawas bylaws and on Islamic criminal law. The theory used in this study is a theory related to the legal sanctions of liquor providers in Islamic criminal law and the legal sanctions of liquor providers in the Padang Lawas Regional Regulation. Furthermore, the type of research used is library research, using a normative juridical approach.The results of the research obtained are that the sanctions given against liquor providers in Article 22 paragraph 1 of Padang Lawas Regional Regulation No.07 of 2015 are a three-month penalty or a fine of Rp.50,000,000 (fifty million rupiah). In Islamic crimes, the sanction has been imposed with the punishment of hadd, namely dera (whipping) as much as 80 (eighty) times, forty times dera (whipping) is a decree of Allah Swt and forty times more is a punishment of ulil amri. The sanctions in Article 22 paragraph 1 of the Padang Lawas Regional Regulation are very light compared to the sanctions given in Islamic criminal law.